2016
DOI: 10.1177/1352458516678934
|View full text |Cite
|
Sign up to set email alerts
|

Closing the gap: Longitudinal changes in employment for Australians with multiple sclerosis

Abstract: The gap in employment between PwMS and the general population has substantially reduced from 2010 to 2013, with organisations responding positively to requests for work role/environment adjustments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 23 publications
1
24
0
Order By: Relevance
“…Our findings consistently showed that those who used higher efficacy DMTs (eg, fingolimod and natalizumab) were two to three times more likely to report that DMTs increased their amount of work, work attendance and work productivity compared with patients who used classical injectable DMTs (β-interferons and glatiramer acetate in our study). Our findings are corroborated by the indirect evidence that the increase in use of higher efficacy DMTs since 2010 aligns with the increased employment rates of people with MS in Australia from 2010 to 201312. Taken together, our study suggest that prescribing higher efficacy DMTs to people with RRMS, particularly those of working age, may bring them significant benefits in work productivity and workforce participation compared with the classical first-line injectable DMTs.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Our findings consistently showed that those who used higher efficacy DMTs (eg, fingolimod and natalizumab) were two to three times more likely to report that DMTs increased their amount of work, work attendance and work productivity compared with patients who used classical injectable DMTs (β-interferons and glatiramer acetate in our study). Our findings are corroborated by the indirect evidence that the increase in use of higher efficacy DMTs since 2010 aligns with the increased employment rates of people with MS in Australia from 2010 to 201312. Taken together, our study suggest that prescribing higher efficacy DMTs to people with RRMS, particularly those of working age, may bring them significant benefits in work productivity and workforce participation compared with the classical first-line injectable DMTs.…”
Section: Discussionsupporting
confidence: 76%
“…We have recently shown that the employment rate of Australians with MS has increased from 48.8% in 2010 to 57.8% in 2013 12. The factors associated with this encouraging improvement are largely unclear but increased availability of more potent DMTs may be an important contributor 13.…”
Section: Introductionmentioning
confidence: 99%
“…Loss of productivity is now responsible for 32% of the costs of MS in Australia ($1.75 billion annually in 2017) [33]. Fortunately, this has reduced from 49% in 2010 [34], likely due to employers providing more work role and/or environment adjustments [35] and improvements in disease modifying therapies [36], enabling people to stay in employment longer. Assisting people to maintain employment will therefore benefit society, PwMS and their families.…”
Section: Discussionmentioning
confidence: 99%
“…An Australian MS Needs Analysis study reported that 66% of participants with mild MS were employed, which decreased to 39% of those with moderate MS and only 9% of those with severe MS. 20 Based on data from the Australian Multiple Sclerosis Longitudinal Study (AMSLS), 48.8% of people with MS were employed either full-time or part-time compared with 63.1% of the Australian general population in 2010, rising to 57.8% in 2013 which was still significantly lower than the general population employment rate of 61.4%. 21 A more recent study also using AMSLS data reported an overall labor force participation rate of 54.7% among working-aged respondents (18-64 years). 22 However, less than 4% of participants in this analysis of work productivity loss had PPMS.…”
Section: Introductionmentioning
confidence: 95%